The Philae lander mission and science overview. (13th July 2017) - Boehnhardt, Hermann; Bibring, Jean-Pierre; Apathy, Istvan; Auster, Hans Ulrich; Ercoli Finzi, Amalia; Goesmann, Fred; Klingelhöfer, Göstar; Knapmeyer, Martin; Kofman, Wlodek; Krüger, Harald; Mottola, Stefano; Schmidt, Walter; et al.
Abstract : The Philae lander accomplished the first soft landing and the first scientific experiments of a human-made spacecraft on the surface of a comet. Planned, expected and unexpected activities and events happened during the descent, the touch-downs, the hopping across and the stay and operations on the surface. The key results were obtained during 12–14 November 2014, at 3 AU from the Sun, during the 63 h long period of the descent and of the first science sequence on the surface. Thereafter, Philae went into hibernation, waking up again in late April 2015 with subsequent communication periods with Earth (via the orbiter), too short to enable new scientific activities. The science return of the mission comes from eight of the 10 instruments on-board and focuses on morphological, thermal, mechanical and electrical properties of the surface as well as on the surface composition. It allows a first characterization of the local environment of the touch-down and landing sites. Unique conclusions on the organics in the cometary material, the nucleus interior, the comet formation and evolution became available through measurements of the Philae lander in the context of the Rosetta mission. This article is part of the themed issue 'Cometary science after Rosetta'.